THE EFFECT OF STORAGE TIME ON TOTAL OF FUNGI IN KANJI PEDAH - Resmila Dewi; Risa Nursanty; Cut Yulvizar (Jurnal Natural, 2011)
The research was conducted to determine the quality of the kanji pedah by counting total number and percentage of Aspergillus flavus and Aspergillus niger. It had been done since March from to October 2010 in Microbiology Laboratory of Biology Departement FMIPA Unsyiah. Kanji pedah as the sample was taken from Meunasah Mesjid Syamtalira village, Aron Subs-district of North Aceh. This research used sample from variety storage time groups range 3-7 days; 5-7 months; 9-12 months; and 15-18 months. Data were analyzed in descriptive and compared with the quality standard from Directorate General of National Agency of Drug and Food Control (Dirjen BPOM RI). The result showed the entire sample had fungi with ranged 1.45-63.7x102. The amount of fungi exceeds the quality standard already established by the National Agency of Drug and Food Control No. 05018/KBPOM/2001: 50 colony/g. Also Aspergillus flavus was found with range from 3%-27% meanwhile Aspergillus niger was found with range from 21,1%-40,9%.